Judging spatio-temporal variability of key river water quality vis-à-vis land use changes in Mahi Basin - PARMAR, URVASHIBEN; GAUR, MURARI LAL (Journal of Soil and Water Conservation, 2023)
Understanding and maintaining healthy river ecosystems is critical to meet the sustained needs of people, livestock, biodiversity, ecology, and whole society. Here good water quality plays a pivotal role in regulating the hazards for farms, farmers, farming, human and animals as whole, industrial and domestic sectors, and also the holistic ecologic constituents. Very little R&D emphasis is paid for evaluating spatial and temporal variabilities of river water cutting across diverse segments of any prevailing basin or catchment. In the present study, the spectrum of river water quality in Mahi river basin located in Western India, is assessed through its physiographic isolation in four different fragments (3729 to 32959 km2). These fragments remained as sub-catchments that formed a loop eventually joining the entire sub-basins/ basin. River water quality related variabilities in different reaches of a basin (upper/middle/lower) has been researched and quantified with logical connectiveness thereupon. The results of the study are based on quantitative assessment of 18 key water quality parameters of the river. Spatio-temporal variability with monthly time steps over a ten-year period (2006-2016); covered entire basin for resulting magnitudes, ranges, and changing patterns of each parameter during dry (January to June) and wet (July to December) annual periods. The comparisons of land use changes (derived via satellite/groundbased records) during identical period and equivalent fluctuations in river water quality indicators; are also examined and compared to arrive appropriate relevancies and relationships. Some of the prevailing shortcomings with suggestions for future work are too also involved.